Molecular Characterization of Novel x-Type HMW Glutenin Subunit 1B × 6.5 in Wheat - Hlozáková, Tímea Kuťka; Gálová, Zdenka; Šliková, Svetlana; Leišová-Svobodová, Leona; Beinhauer, Jana; Dyčka, Filip; Šebela, Marek; Zetochová, Erika; Gregová, Edita (Plants (Basel, Switzerland), 2021)
A novel high molecular weight glutenin subunit encoded by the Glu-1B locus was identified in the French genotype Bagou, which we named 1B × 6.5. This subunit differed in SDS-PAGE from well-known 1B × 6 and 1B × 7 subunits, which are also encoded at this locus. Subunit 1B × 6.5 has a theoretical molecular weight of 88,322.83 Da, which is more mobile than 1B × 6 subunit, and isoelectric point (pI) of about 8.7, which is lower than that for 1B × 6 subunit. The specific primers were designed to amplify and sequence 2476 bp of the Glu-1B locus from genotype Bagou. A high level of similarity was found between the sequence encoding 1B × 6.5 and other x-type encoding alleles of this locus.
Keywords: wheat; 1-D electrophoresis; mass spectrometry; 2-D electrophoresis; HMW glutenin